2019
DOI: 10.1111/asj.13219
|View full text |Cite
|
Sign up to set email alerts
|

Effects of resveratrol treatment on mitochondria and subsequent embryonic development of bovine blastocysts cryopreserved by slow freezing

Abstract: This study evaluated the effects of cryopreservation by slow freezing on the mitochondrial function, DNA integrity, and developmental ability of bovine embryos and examined whether resveratrol treatment of the frozen‐thawed blastocysts improved embryonic viability. In vitro produced bovine embryos were subjected to slow freezing. After thawing, the ATP content and mitochondrial DNA integrity (mtDNA), determined by real‐time PCR targeting short and long mitochondrial sequences, was found to be lower in frozen‐t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…When granulosa cells were treated with mitochondrial uncoupler inducing mitochondrial dysfunction, the amount of cf-mtDNA in the medium increased [44]. Vitrification tends to affect the levels of cf-mtDNA in the SCM of bovine embryos, as does the treatment of vitrifiedwarmed embryos with resveratrol, which was previously reported to improve embryonic development and increases cf-mtDNA content in the medium [22,45]. In addition, it has been reported that the inhibition of autophagy increases the cf-mtDNA content and that the inhibition of either proteasome or intracellular vesicle formation decreases cf-tDNA content in the SCM of bovine granulosa cells [41].…”
Section: Discussionmentioning
confidence: 95%
“…When granulosa cells were treated with mitochondrial uncoupler inducing mitochondrial dysfunction, the amount of cf-mtDNA in the medium increased [44]. Vitrification tends to affect the levels of cf-mtDNA in the SCM of bovine embryos, as does the treatment of vitrifiedwarmed embryos with resveratrol, which was previously reported to improve embryonic development and increases cf-mtDNA content in the medium [22,45]. In addition, it has been reported that the inhibition of autophagy increases the cf-mtDNA content and that the inhibition of either proteasome or intracellular vesicle formation decreases cf-tDNA content in the SCM of bovine granulosa cells [41].…”
Section: Discussionmentioning
confidence: 95%
“… 7 , 8 , 9 In our studies based on porcine oocytes, bovine eight‐cell stage and blastocyst stage embryos, ATP content, mitochondrial genome integrity and developmental ability in cryopreserved samples was low compared with those fresh counterparts. 10 , 11 , 12 A previous study showed that vitrification of ovine oocytes induced low mitochondrial function and high ROS content; however, optimal restoration period, in this case 4 hours after vitrification‐warming partly improved oocyte developmental ability. 13 However, little is known about the restoration of mitochondria after the warming of oocytes and embryos.…”
Section: Introductionmentioning
confidence: 80%
“… 64 In this context, resveratrol increased mitochondrial cell‐free DNA in the culture medium of cryopreserved‐warmed embryos and concomitantly, decreased mitochondrial DNA copy number and protein levels in the embryos. 10 , 11 …”
Section: Mitochondrial Dysfunction and Degradationmentioning
confidence: 99%
“…Besides, SIRT1 expression and cell-free mtDNA content in the medium were higher in the case of embryos treated with resveratrol. It should be noted that slow freezing affects mitochondrial integrity and function in blastocysts (Hayashi et al, 2019). It is important to improve in vitro maturation (IVM) conditions for immature oocytes after cryopreservation, especially if a limited number of oocytes are collected from specific donors.…”
Section: Genetics Of Cryostability Of Reproductive Cellsmentioning
confidence: 99%